Factors influencing the labour market insertion of undergraduate graduates from Peruvian universities - Judith Soledad Yangali Vicente, Pedro Yvan Saenz Rivera, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of the research was to propose that some socio-demographic factors: gender, economic level and parents' education; basic education factors such as the department and type of secondary education management and mainly undergraduate and postgraduate factors measured by the characteristics of the university-career explain the insertion of university graduates in the Peruvian labour market. The quantitative, theoretical and explanatory approach study consisted of the analysis of information received from the Ministry of Education, a sample of 8072 graduates from 2014-2017 from a total of 15 private universities and 35 state universities. We found 50% of graduates employed with adequate hours, wages and tasks, 21% with inadequate employment and the remaining 29% unemployed. Using the multinomial logistic regression model, it was shown that engineering degrees have 4 times the employment opportunity, while graduating from a university in the first places in the Research Ranking favours employment by around 50%, gender, department, family income and the mother's level of education are also factors that condition employment insertion.